1999
DOI: 10.2169/internalmedicine.38.426
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hyponatremia Caused by Hypothalamic Adrenal Insufficiency.

Abstract: A 60-year-old womanwas admitted with severe hyponatremia. Basal values of adrenocorticotropic hormone (ACTH), thyroid hormone and cortisol were normal on admission. Impairment of water diuresis was observed by water loading test. Initially, we diagnosed her condition as the syndrome of inappropriate secretion of antidiuretic hormone(SIADH). By provocation test, we finally confirmed that the hyponatremia was caused by hypothalamic adrenal insufficiency. The basal values ofACTHand cortisol might not be sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Shibata et al [14] reported a similar case with severe hyponatremia in which the basal serum cortisol level was 12.1 lg/dL. The patient's hyponatremia fulfilled the criteria of SIADH used in Japan, but was normalized by the administration of hydrocortisone.…”
Section: Discussionmentioning
confidence: 89%
“…Shibata et al [14] reported a similar case with severe hyponatremia in which the basal serum cortisol level was 12.1 lg/dL. The patient's hyponatremia fulfilled the criteria of SIADH used in Japan, but was normalized by the administration of hydrocortisone.…”
Section: Discussionmentioning
confidence: 89%
“…Cortisol being an inhibitor of ADH secretion, hence low level of cortisol leads to increased ADH secretion and resulting in decreased excretion of water by the kidney and subsequently causing hyponatremia [6]. It has also been shown that loss of suppression of the osmostat for ADH release could be the underlying mechanism for ADH hypersecretion in adrenal insuffi ciency [7]. Thus, the benefi t of corticosteroid replacement is thought to be mainly due to suppression of ADH.…”
Section: Discussionmentioning
confidence: 99%
“…Serum arginine vasopressin (AVP) was inappropriately high in relation to low serum osmolality in these patients. Shibata et al (7) confirmed that the ADHsecretion increased inappropriately to osmolality and the osmotic threshold of ADHsecretion increased after glucocorticoid administration in their patient with adrenal insufficiency due to hypothalamic dysfunction who was initially diagnosed as SIADHin this issue of Internal Medicine.…”
mentioning
confidence: 92%